Complete chloroplast genome sequence of Oxytropis glabra (Leguminosae). Issue 9 (2nd September 2021) - Liu, Shuo; Li, Ya-Rui; Si, Wei; Qu, Wen-Rui; Yang, Tian-Ge; Wu, Zhi-Hua; Jiao, Pei-Pei
Abstract: Oxytropis glabra DC. is a perennial poisonous plant to livestock belonging to the genus Oxytropis, Leguminosae, mainly distributed in Northwestern China. As a poisonous grass, this species protects plant diversity in degraded grasslands by sheltering adjacent plants. In this study, the complete chloroplast genome with a total size of 122, 094 bp was reported. Our annotations showed that the chloroplast genome contains 109 genes, including 76 protein-coding genes, 29 tRNA genes, and four rRNA genes. This work presents complete chloroplast genome information, which will be valuable for studying the evolution and genetic diversity of O. glabra.